The higher degree by research student as ‘master’: Utilising a design thinking approach to improve learner experience in higher degree research supervision - van der Laan, Luke; Ormsby, Gail; Fergusson, Lee; Pau, Maria (Journal of University Teaching and Learning Practice, 2021)
This article presents a work-based learning and research approach to professional postgraduate education specifically in the case of Higher Degree by Research (HDR) programs. It highlights a prototype of the Cohort-based Advisory Team (CAT) model as a useful strategy. The authors propose that a design thinking approach that empathises with the student experience as the “Master” of the design reveals insights that may inform future formal higher education in the professions. An overview of the design thinking process associated with the Professional Studies programs as developed at the University of Southern Queensland (USQ) is provided. Case accounts of HDR students in the law and engineering disciplines provide exploratory evidence of the student experience. The article concludes that there is a case to be made to professional associations that this form of professional development (work-based learning and research) should be recognised in terms of the contributions it makes to the knowledge, skills and abilities of graduates.